2022
DOI: 10.3389/fenvs.2022.964327
|View full text |Cite
|
Sign up to set email alerts
|

A study on the impact of fiscal decentralization on carbon emissions with U-shape and regulatory effect

Abstract: The Chinese government set a goal in 2009 to cut carbon emissions by 40–45 percent of 2005 GDP per unit by 2020. The role of fiscal decentralization reform in strengthening environmental governance has gained importance. This paper explored the impact of fiscal decentralization reform from 2010 to 2019 on carbon dioxide emissions in China. We utilized the first-order differential dynamic panel econometrics model to examine the correlation between fiscal decentralization and carbon dioxide emission under fiscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Environmental governance, such as carbon emission reduction, is a typical principal-agent problem in which the central government, local governments and enterprises play different roles in the collaborative governance process. Vertical transfer system essentially reflects the principal-agent relationship between the central government and local governments, with the central government as the principal and local governments as the agent (Xia et al, 2022). With the goal of promoting local economic development and energy saving and emission reduction, the central government reaches a long-term contract with local governments and compensates them with transfer payments.…”
Section: Vertical Transfers and Carbon Emissionsmentioning
confidence: 99%
“…Environmental governance, such as carbon emission reduction, is a typical principal-agent problem in which the central government, local governments and enterprises play different roles in the collaborative governance process. Vertical transfer system essentially reflects the principal-agent relationship between the central government and local governments, with the central government as the principal and local governments as the agent (Xia et al, 2022). With the goal of promoting local economic development and energy saving and emission reduction, the central government reaches a long-term contract with local governments and compensates them with transfer payments.…”
Section: Vertical Transfers and Carbon Emissionsmentioning
confidence: 99%
“…Cheng et al ( 2020b ) assessed the nonlinear effect of fiscal decentralization on ecological sustainability in China using a dynamic panel data methodology and the logarithmic mean Divisia index decomposition approach. Xia et al ( 2022a ) posited that fiscal decentralization in eastern China had made a significant contribution to the performance of environmental governance. They used panel data from 31 provinces from 2010 to 2019 to compare the influence on regional carbon emissions.…”
Section: Literature Review and Contributions Of The Studymentioning
confidence: 99%
“…In another research on fiscal decentralization in case of China, China, Xia et al (2021) detected the favorable impact of carbon emissions in diverse regions, while environmental decentralization tends to decrease those emissions. The different impacts between FISDEC and CO2 in different regions might occur due to different industries alongside different income structures ( Xia et al, 2022 ). In novel research in Chinese provinces, Zhu et al (2022) observed the significant impact of EXDEC on CO2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But then again with efficient use of decentralization (REVDEC or EXDEC), human capital, and resource rents, the environmental quality can be enhanced, which is imperative for a sustainable future. However, the impact of increasing economic activities increase CO2 emissions in most economies ( Ganda, 2022 ; Malik et al, 2020 ; Wang et al, 2022 ; Wang et al, 2022a ; Raihan and Tuspekova, 2022 ; Kirikkaleli et al, 2022 ; Safdar et al, 2022 ; Huang and Guo, 2022 ; Safi et al, 2022 ; Xia et al, 2022 ). But the study uses a combined degree of decentralization, including both revenue and expenditure decentralization which refers to the transfer of authority, responsibility, and resources to lower levels of government that is a new input in the case of decentralized nations.…”
Section: Literature Reviewmentioning
confidence: 99%